Pengaruh Profitabilitas, Ukuran Perusahaan dan Intensitas Modal Terhadap Tax Avoidance (Studi Kasus pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Listing di Bursa Efek Indonesia 2018-2021) - Fadilah Nurul Khairat; Ingra Sovita Sovita (CV. ITTC INDONESIA, 2023)
Differences in interests between taxpayers and the government lead to tax avoidance actions carried out by taxpayers, one of which is by taking advantage of loopholes in tax legislation. This study aims to determine and analyze the effect of profitability, firm size and capital intensity on tax avoidance. The sample in this study is a food and beverage sub-sector manufacturing company for the 2018-2021 period. The sample selection technique used a purposive sampling method in order to obtain a sample of 13 companies with 56 observational data. Testing was carried out with the help of SPSS (Statistical Product and Service Solution) and data analysis using in this study using multiple linear regression analysis. The results showed that firm size has a significant negative effect on tax avoidance, while profitability and capital intensity have no effect on tax avoidance.